2022
DOI: 10.1007/s11356-022-19627-8
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metals and metalloid levels in the tissues of yellow-legged gulls (Larus michahellis) from Spain: sex, age, and geographical location differences

Abstract: In the present study, mercury (Hg), cadmium (Cd), lead (Pb), selenium (Se), and arsenic (As) were measured in liver, kidney, and feathers of adult, juvenile, and chick seagulls (Larus michahellis) collected from the northwest of Spain. Age, sex, and the geographical location of samples were considered variables that can influence metal bioaccumulation, for which concentrations were determined by means of ICP-MS. The mean concentrations (dry weight) found in seagulls were 7.01 ± 0.37 mg Hg/kg, 22.82 ± 2.83 mg C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 80 publications
(114 reference statements)
0
1
0
Order By: Relevance
“…Our findings show a lack of statistically significant differences between males and females in the contents of essential and non-essential elements in the tissues of wild boar; except for As, which was significantly higher in the liver of males ( Table 5 ). The influence of sex on the bioavailability, the transfer and the effects of contaminants and other elements has been evaluated in several studies with different and sometimes conflicting results [ 56 ]. Generally, the contents of essential and non-essential elements can be influenced by factors such as the metabolic rate, hormonal pattern and reproductive state [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our findings show a lack of statistically significant differences between males and females in the contents of essential and non-essential elements in the tissues of wild boar; except for As, which was significantly higher in the liver of males ( Table 5 ). The influence of sex on the bioavailability, the transfer and the effects of contaminants and other elements has been evaluated in several studies with different and sometimes conflicting results [ 56 ]. Generally, the contents of essential and non-essential elements can be influenced by factors such as the metabolic rate, hormonal pattern and reproductive state [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…The increased sample sizes for all the groups of birds are required to better understand the differences in the deposition patterns of the metals in these bird species. Previous studies have revealed gender and age differences in the accumulation of heavy metals in birds [57,58]; nonetheless, we did not consider sex-depended differences in metal accumulation, and most of the tissue samples were collected from adult birds. In addition to gathered bird organs, the analyses of other environmental samples such as soil, water, and bird feed are also critical to identify the sources and pathways of heavy metal contamination in these wild birds.…”
Section: Discussionmentioning
confidence: 99%